2006
DOI: 10.1007/s00280-006-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study with the combination of gemcitabine and DTIC in patients with advanced soft tissue sarcomas

Abstract: Although the remission rate was low, PFR figures indicate that this regimen has activity in patients with ASTS. It should be compared with DTIC, or other gemcitabine-containing combinations, in patients with LMS or MFH, to determine whether this combination offers advantages in PFR or in overall activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Combined with vinorelbine in a 40-patient study, gemcitabine produced a clinical benefit response rate (CBR), defined as the sum of ORR and SD of 25% at 4 months [67]. Another small study of gemcitabine/dacarbazine yielded low ORR in 4%, but SD in 72.6% of patients [68]. Gemcitabine and dacarbazine were further explored in a randomized phase 2 trial enrolling 113 patients, assessing the progression-free rate (PFR) at 3 months [69•].…”
Section: Taxanes and Gemcitabinementioning
confidence: 96%
“…Combined with vinorelbine in a 40-patient study, gemcitabine produced a clinical benefit response rate (CBR), defined as the sum of ORR and SD of 25% at 4 months [67]. Another small study of gemcitabine/dacarbazine yielded low ORR in 4%, but SD in 72.6% of patients [68]. Gemcitabine and dacarbazine were further explored in a randomized phase 2 trial enrolling 113 patients, assessing the progression-free rate (PFR) at 3 months [69•].…”
Section: Taxanes and Gemcitabinementioning
confidence: 96%
“…Regarding combination therapy for second-line treatment in advanced STS, there are a few data on clinical trials comparing different schedules. e combination of gemcitabine and dacarbazine has activity in patients with previously treated STS [41][42][43], with a better tolerance profile than the one observed with the combination of gemcitabine and docetaxel in the SARC002 study [44]. To be specific, the rate of progression-free survival (PFS) after three months of treatment with the combination of gemcitabine and dacarbazine was 46% in the study by Losa et al [41] and 56% in the one conducted by García del Muro et al [42].…”
Section: Sarcomamentioning
confidence: 99%
“…57,58 Phase II studies of gemcitabine in combination with either vinorelbine or dacarbazine, showed only limited efficacy for STS. 5961 Meanwhile, docetaxel is a taxane with microtubule-inhibiting activity, and also has single-agent activity as second-line therapy. 62,63 Given that GD have different mechanisms of action from either anthracyclines or alkylating agents, as well as preclinical evidence of their synergy, there was rationale for combining these agents for treating STS.…”
Section: Gemcitabine and Docetaxelmentioning
confidence: 99%